1984
DOI: 10.1111/j.1600-0714.1984.tb01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Lectin‐binding in premalignant lesions during submandibular gland carcinogenesis

Abstract: Complex carbohydrates in premalignant lesions of mouse submandibular gland tumors were examined by the lectin‐peroxidase conjugate method. Peroxidase‐conjugated lectins of PNA, RCA‐1, DBA, SBA, UEA‐1 and WGA were used to detect specific sugar residues of complex carbohydrates in premalignant lesions during experimental carcinogenesis. Marked reduction of PNA and SBA bindings occurred in duct‐like structures and cystic lesions which were transformed from granular convoluted tubule cells. Premalignant lesions bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It has been reported that .salivary gland myoepithelial cells stain for myosin, actomyosin (30,31), and actin (18). tions for FXiF, NCiF and leetins are reduced in proportion to the degree of degranulation of granular eonvoluted tubule cells and staining finally disappears (It), 12,24). Salivary gland growth factors such as E£(JF and NCiF, and leetin-bmding reaetions for sugar residues are thus useful as histochemical markers for the specific detection of granular convoluted tubule cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that .salivary gland myoepithelial cells stain for myosin, actomyosin (30,31), and actin (18). tions for FXiF, NCiF and leetins are reduced in proportion to the degree of degranulation of granular eonvoluted tubule cells and staining finally disappears (It), 12,24). Salivary gland growth factors such as E£(JF and NCiF, and leetin-bmding reaetions for sugar residues are thus useful as histochemical markers for the specific detection of granular convoluted tubule cells.…”
Section: Discussionmentioning
confidence: 99%
“…The granular convoluted tubule cells, target cells for chemical eareinogenesis, contain epidermal growth factor (EGF), nerve growth factor (N(iF) (K-IO), and eomplex carbohydrates whieh .specifically bind lectins (11). These particular substances in granular convoluted tubule eells were altered during eareinogenesis (12).…”
mentioning
confidence: 97%
“…Further they could play important role in immune system cell grow and cell dead. On the other hand, lectins could be considered as appropriate tools for monitoring of changes in spectra of glycosides present on surface of cell plasma membrane associated with transformed cell metabolism during cancer development (Murase et al 1984). It could be also applicable for monitoring of surface glycosides alteration during P-gp mediated MDR development (reviewed in Breier et al 2013).…”
Section: Application Of Lectins In Characterization Of Surface Sugarsmentioning
confidence: 99%
“…While MuRASE et at. (29) showed that WGA binding was restricted to the mucous cells and the cystic contents in the mueoepidermoid carcinoma, we found that WGA can bind to all cell types and also to the cystic contents in this neoplasm.…”
Section: Discussionmentioning
confidence: 50%